Loss of FAM134B increased endoplasmic reticulum stress and induced cell autophagy in breast cancer - Zhang, Zhaoqi; Fang, Yan; Qiu, Zhibing; Ding, Shuning; Liu, Deyue; Huang, Wanqiu; Zhu, Li (Frontiers in Immunology, 2025)
ObjectiveBreast cancer is a leading cause of cancer-related mortality, and the most prevalent malignant neoplasm amongst women worldwide. This study aimed to explore the role of FAM134B in breast cancer progression.MethodsThe correlation between FAM134B expression and the prognosis of breast cancer patient was analyzed using the Kaplan-Meier Plotter database. qRT-PCR was used to quantify FAM134B mRNA level, whereas western blotting was employed to detect th expression of FAM134B, autophagy-associated proteins, and endoplasmic reticulum (ER) stress related proteins. Cell proliferation was assessed via CCK-8 and colony formation assays. Cell apoptosis rate was measured by flow cytometry. Autophagosomes formation was observed under a transmission electron microscopy, and the expression of LC3 protein in cells was detected by immunofluorescence. The in vivo function of FAM134B was verified using a tumor xenograft model in nude mice.ResultsHigh expression of FAM134B in breast cancer patients was correlated with reduced overall survival and disease-free survival. Both FAM134B mRNA and protein levels were significantly higher in breast cancer cells than normal breast epithelial cells. Downregulation of FAM134B suppressed the proliferation of breast cancer cells and increased their apoptosis rates. Furthermore, silencing FAM134B triggered autophagy and ER stress in breast cancer. In nude mice, FAM134B knockdown also inhibited breast cancer progression and induced autophagy.ConclusionDownregulation of FAM134B inhibited the development of breast cancer through inducing apoptosis, autophagy, and ER stress of breast cancer cells.